Feeding problems in merosin deficient congenital muscular dystrophy. Issue 6 (1st June 1999) - Philpot, J; Bagnall, A; King, C; Dubowitz, V; Muntoni, F
Abstract : Feeding difficulties were assessed in 14 children (age range 2–14 years) with merosin deficient congenital muscular dystrophy, a disease characterised by severe muscle weakness and inability to achieve independent ambulation. Twelve of the 14 children were below the 3rd centile for weight. On questioning, all parents thought their child had difficulty chewing, 12 families modified the diet, and 13 children took at least 30 minutes to complete a meal. On examination the mouth architecture was abnormal in 13 children. On videofluoroscopy only the youngest child (2 years old), had a normal study. The others all had an abnormal oral phase (breakdown and manipulation of food and transfer to oropharynx). Nine had an abnormal pharyngeal phase, with a delayed swallow reflex. Three of these also showed pooling of food in the larynx and three showed frank aspiration. These six cases all had a history of recurrent chest infections. Six of eight children who had pH monitoring also had gastro-oesophageal reflux. As a result of the study five children had a gastrostomy, which stopped the chest infections and improved weight gain. This study shows that children with merosin deficient congenital muscular dystrophy have difficulties at all stages of feeding that progress with age. Appropriate intervention can improve weight gain and reduce chest infections. The severity of the problem has not been previously appreciated in this disease, and the study shows the importance of considering the nutritional status in any child with a primary muscle disorder.